Recovering out loud: evaluations of coworkers' reactions to soberversary disclosure on social media - Lynner, Brittany N., author; Prasad, Joshua, advisor; Fisher, Gwenith, committee member; Miller, Reagan, committee member; Few, Meara, committee member (Colorado State University. Libraries, 2025)
Soberversaries, anniversaries commemorating one's sobriety from substance misuse, have gained visibility on social media platforms, including LinkedIn, yet little is understood about how individuals manage this concealable stigmatized identity and how colleagues respond. This study investigated identity management strategies employed in LinkedIn soberversary posts and their impact on colleagues' impressions and behavioral intentions, considering the moderating role of workplace substance use norms. Drawing on identity management and impression management literatures, the present study employed a sequential qualitative-quantitative approach (Creswell & Plano Clark, 2018). Qualitative content analysis identified seven identity management strategies, loosely aligning with Roberts' (2005) framework. These findings informed the development of vignettes tested in a between-subjects survey analyzed via structural equation modeling (SEM). Identity management strategies had no significant effects on impressions or behavioral intentions, nor did workplace substance use norms moderate these relationships. Indirect effects were also nonsignificant. However, authentic and archetypal impressions were associated with increased boosterism, and authentic impressions were associated with decreased ostracism. The study advances understanding of stigma management on professional platforms, highlighting narrative framing strategies for individuals in recovery.
Keywords: identity management; ostracism; social media; impression management; disclosure; recovery